An experimental model for mixed friction during running-in - Nogueira, I. (2002)
Mechanical engineering often uses fluid lubrication to limit friction. Even in the presence of a lubricant, metallic contact between the sliding surfaces may readily occur. In running-in, the oil film thickness can be so thin that contact arises at the summit of asperities, thus, increasing both the friction coefficient and wear. Such regimes are the so-called mixed or boundary lubrication. In these situations, the friction coefficient varies continuously and it is therefore, necessary to calculate the friction coefficient at any given moment.